Diplomasi Korea Selatan Dengan Memanfaatkan Olimpiade Musim Dingin Tahun 2018 Untuk Membangun Hubungan Yang Harmonis Dengan Korea Utara - Ambarwati, Ambarwati; Hartati, Anna Yulia (Kajian Hubungan Internasional, 2022)
The Olympics is not merely a major sporting event in the world. However, the Olympics are also a means of diplomacy and as an intermediary for dialogue and building harmonious relations between countries in the world. Through Sport Diplomacy, sport becomes an arena for creating peace. In 1971 sport was used as a tool to reduce conflict between China and America. In 1972 hockey diplomacy also succeeded in creating harmony between Canada and the Soviet Union, and in 2011 cricket diplomacy became a catalyst for improving geopolitical relations between Pakistan and India. Reflecting on this in 2018, South Korea which was appointed to host the Winter Olympics tried to take advantage of this momentum to build harmonious relations with North Korea and create peace on the Korean Peninsula through four mechanisms: Image-building, building a platform dialogue, trust building , Reconciliation, integration and anti-racism